Searching : the theory and practice of making cultural change - Emery, Merrelyn (Dialogues on work and innovation, 1999)
Searching explains how to make the fundamental cultural change required for a desirable sustainable future. It describes the 'two-stage model' of open-systems social science in action and covers two major methods: the Search Conference for strategic planning and community development; and the Participative Design Workshop for the genotypical design and redesign of organizational structures. The result of nearly 50 years of integrated conceptual and practical development, Searching shows that by replacing 200 years of mechanistic assumptions with concepts and principles which accurately capture.